2013
DOI: 10.1001/jamadermatol.2013.6101
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Self-report in Assessing Fitzpatrick Skin Phototypes I Through VI

Abstract: clinicaltrials.gov Identifier: NCT01124513.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
132
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(143 citation statements)
references
References 27 publications
3
132
2
1
Order By: Relevance
“…Reflected skin color, a correlate of melanin content (14, 15), was objectively recorded (mean of 6 readings) from both the outer and inner part of the subject's left upper arm using a BYK-Gardner CGSS (Geretsried, Germany) hand-held reflectance spectrophotometer with standard reflectance at 685 nm, calibrated before each session. The multi-wavelength data quantify color using the Commission Internationale de l'Éclairage L* a* b* color space parameters: with dimension L* indicating lightness of color (smaller values indicate darker color), a* the position between red and green and b* the position between yellow and blue (smaller values indicate lighter color) (16).…”
Section: Methodsmentioning
confidence: 99%
“…Reflected skin color, a correlate of melanin content (14, 15), was objectively recorded (mean of 6 readings) from both the outer and inner part of the subject's left upper arm using a BYK-Gardner CGSS (Geretsried, Germany) hand-held reflectance spectrophotometer with standard reflectance at 685 nm, calibrated before each session. The multi-wavelength data quantify color using the Commission Internationale de l'Éclairage L* a* b* color space parameters: with dimension L* indicating lightness of color (smaller values indicate darker color), a* the position between red and green and b* the position between yellow and blue (smaller values indicate lighter color) (16).…”
Section: Methodsmentioning
confidence: 99%
“…From May to July 2014, a cross-sectional study compared survey responses: color bar tool, skin tone descriptions and the adapted Fitzpatrick skin type questions. 2 Participants’ melanin index was obtained using spectrophotometry (Mexameter MX18 probe, Corage + Khazaka Electronic GmbH, Koln, Germany).…”
mentioning
confidence: 99%
“…As part of this evolution, the original 4 skin types (I-IV), which assessed sun reactivity with standardized questions about the ease of sun burning and tanning reactions to the first exposure in the summer, were modified by adding SPT V and VI to include those with brown and black skin [1] . Our research demonstrated that the modifications to include people with skin of color were neither culturally sensitive nor accurate, as people of color were unable to respond to the questions of sunburn and tanning [20][21][22] . People with deep pigmentation of the skin did not report turning red or pink but rather experienced "irritation" after sun exposure [20][21][22].…”
Section: Resultsmentioning
confidence: 79%
“…Our research demonstrated that the modifications to include people with skin of color were neither culturally sensitive nor accurate, as people of color were unable to respond to the questions of sunburn and tanning [20][21][22] . People with deep pigmentation of the skin did not report turning red or pink but rather experienced "irritation" after sun exposure [20][21][22]. Another limitation of the six Roman numeral Fitzpatrick SPT integers was the reliance upon a history of sunburn after the first exposure of summer.…”
Section: Resultsmentioning
confidence: 79%